A simple 1-D finite elements approach to model the effect of PCB in electronic assemblies. (March 2016) - Chiozzi, D.; Bernardoni, M.; Delmonte, N.; Cova, P.
Abstract: In this paper, a simple method to describe the effect of Printed Circuit Board (PCB) and environment on the thermal behavior of packaged devices is addressed. This approach aims at exploiting the benefit of compact thermal models, which are necessarily one-dimensional, together with the advantage of Finite Element (FE) modeling, which retains all the three-dimensional geometrical details, only in the regions of the model that must be accurately described. The main focus is on correct modeling of long power pulses for subsequent electro-thermal and thermo-mechanical analysis at chip level. Highlights: A method to account for effects of PCB on thermal behavior of devices is proposed. Advantages of compact models together with those of 3D FEM are exploited. Correct thermal modeling of transients related to long power pulses is allowed.